Cutis marmorata telangiectatica congenita - Mocan, Hilal; Özbay, Gamze; Alhan, Ethem; Özoran, Yavuz; Özdemir, Mustafa (The Turkish Journal of Pediatrics, 1985)
The case of a 3-year-old boy with cutis marmorata telangiectatica congenita is presented. This is believed to be the first report of its kind from Turkey.
Keywords: congenital generalized phlebectasia; cutis marmorata telangiectatica congenita (CMTC)